Implementasi Aromaterapi Mawar Untuk Mengurangi Kecemasan Pre Operasi Pada Pasien Sectio Caesarea Dengan Anestesi Spinal - Auliya, Khidmatul; Suryani, Roro Lintang; Yudha, Magenda Bisma (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: A cesarean section is a risky operation that could make some people anxious. Failure to alleviate patient anxiety during a cesarean section might compromise the patient's ability to undergo the procedure since it affects their circulatory, gastrointestinal, respiratory, and muscular systems. Rose aromatherapy is one of the non-pharmacological methods that may be used to manage anxiety prior to surgery. Objective: Patients undergoing spinal anesthesia for a caesarean section might benefit from this community service project's non-pharmacological methods of anxiety reduction, which included the use of rose aromatherapy. Method: As a community service project, we inhale rose aromatherapy for four minutes after placing a cotton ball about two centimeters from the patient's nose and adding six drops of rose aromatherapy to it. Result: According to the findings of this community service project, thirteen participants (43.3%) reported moderate anxiety and seventeen (56.7%) reported severe anxiety prior to the use of rose aromatherapy. A total of 11 subjects (36.7%) reported mild anxiety, 18 reported moderate anxiety (60%) and 1 reported severe anxiety (3.3%) after receiving rose aromatherapy. Conclusion: Based on the results of this Community Service activity, it can be concluded that rose aromatherapy can reduce preoperative anxiety in patients who will perform sectio caesarea.